Urban tree planting programs, function or fashion? Los Angeles and urban tree planting campaigns - Pincetl, Stephanie; Gillespie, Thomas; Pataki, Diane E.; Saatchi, Sassan; Saphores, Jean-Daniel (GeoJournal, 2013)
Tree planting programs are being implemented in many US cities (most notably New York, Los Angeles, and Chicago) on the basis of the multiple environmental and health benefits they may provide. However, the magnitude and even the direction of the impacts of trees on specific urban environments have seldom been directly measured. In addition, there has been little research on the historical, cultural, political or institutional origins of such programs, or on their implementation process. Pending questions include the degree to which these programs are integrated in the existing frameworks of city government and infrastructure management, how they are paid for, and the kinds of collaborations between nonprofit organizations, the public, and public agencies at all levels they may require in order to succeed. This paper reports on an interdisciplinary research project examining the Million Tree Program of the City of Los Angeles.